Current Research in Nuclear Reactor Technology in Brazil and Worldwide - Zacarias Mesquita, Amir (IntechOpen, 2013)
The aim of this book is to disseminate state-of-the-art research and advances in the area of nuclear reactors technology. The book was divided in two parts.Topics discussed in the first part of this compilation include: experimental investigation and computational validation of thermal stratification in PWR reactors piping systems, new methods in doppler broadening function calculation for nuclear reactors fuel temperature, isothermal phase transformation of uranium-zirconium-niobium alloys for advanced nuclear fuel, reactivity Monte Carlo burnup simulations of enriched gadolinium burnable poison for PWR fuel, utilization of thermal analysis technique for study of uranium-molybdenum fuel alloy, probabilistic safety assessment applied to research reactors, and a review on the state-of-the art and current trends of next generation reactors. The second part includes: thermal hydraulics study for a ultra high temperature reactor with packed sphere fuels, benefits in using lead-208 coolant for fast reactors and accelerator driven systems, nuclear power as a basis for future electricity production in the world: Generation III and IV reactors, nanostructural materials and shaped solids for improvement and energetic effectiveness of nuclear reactors safety and radioactive wastes, multilateral nuclear approach to nuclear fuel cycles, and a cold analysis of the Fukushima accident.